Exploring Farmers' Reasons for Antibiotic Use and Misuse in Pig Farms in Brazil - Rita Albernaz-Gonçalves; Gabriela Olmos; Maria José Hötzel (MDPI AG, 2021)
Stressful management that makes farmed pigs susceptible to infections is associated with high antibiotic use (AMU) and resistance (AMR). Pig farmers are key stakeholders to support the international agenda pushing AMU restrictions. We interviewed 58 pig farmers on AMU/AMR, biosecurity, veterinary assistance, disease prevention and treatment, aiming to understand practices and attitudes towards the AMU/AMR problem. Farmers described a reliance on antibiotics to prevent and treat disease while neglecting biosecurity measures. We identified inappropriate AMU practices (high use of broad-spectrum antibiotics, incorrect dosage or treatment length) and unrestricted access to antibiotics, which encouraged imprudent AMU. Nevertheless, most farmers considered this AMU legitimate to guarantee herd productivity and showed unpreparedness and resistance to changing AMU practices, perceiving limitations (economic, sanitary and inspection) more easily than alternatives to reduce AMU. Agro-industries and foreign markets were mentioned, and internal consumers dismissed as potential motivators for behavioral changes. Importantly, farmers' economic, technical and social factors may limit their autonomy to change practices. We conclude that the observed distancing of pig farmers from the AMU/AMR problem limits the efficiency of policies aiming for a prudent AMU. Our study indicates a need for education, training and behavior change nudging that should include other stakeholders beyond farmers.